Experimental study on the mechanical behavior of high-stress rocks during real-time drilling - Zhichao He; Fengqiang Gong; Mingzhong Gao (International Journal of Coal Science & Technology)
Abstract The formation of a pressure relief zone is crucial for rockbust prevention during drilling pressure relief. This study investigates the mechanical behavior of high-stress rock under real-time drilling conditions and elucidates the mechanism behind the creation of the pressure relief zone. Utilizing the independently developed SG4500 drilling rig, we conducted a theoretical analysis of the forces acting on the drill bit. The analysis showed that cutting depth is directly proportional to real-time drilling speed, while tangential and normal forces are influenced by drilling diameter. Uniaxial compression tests on red sandstone specimens under high-stress real-time drilling conditions examined the impacts of different drilling speeds (800, 400, 100 r/min) and diameters (6, 8, 10, 12 mm) on rock mechanical behavior, rockburst characteristics, crack evolution, and peak elastic strain energy. The results indicate that decreasing drilling speed and increasing drilling diameter weaken rock mechanical behavior, including peak strength, Young’s modulus, rockburst characteristics, and peak elastic strain energy. Crack evolution analysis reveals that smaller drilling diameters and higher drilling speeds promote the development of far-field cracks, while larger drilling diameters and lower drilling speeds lead to crack formation around the borehole, and significantly affecting rock failure mechanisms. Theoretical analysis further confirms the correlation between crack evolution and stress distribution surrounding the drilling. Under vertical stress, the cracks near the borehole formed during real-time drilling are mainly influenced by tangential compressive and tensile stresses. Overall, this study provides a new perspective on understanding the mechanisms of drilling pressure relief for rockburst prevention.